History of Antibiotics: From Fluoroquinolones to Daptomycin (Part 2). (1st August 2013) - Zaffiri, Lorenzo; Gardner, Jared; Toledo-Pereyra, Luis H.
ABSTRACT: In the Modern Era, physicians attested to the reciprocal influence among a technologically advanced society, rapid scientific progresses in medicine, and the need for new antimicrobials. The results of these changes were not only seen in the prolongation of life expectancy but also by the emergence of new pathogens. We first observed the advent of Gram-negative bacteria as a major source of nosocomial infections. The treatment of these microorganisms was complicated by the appearance and spread of drug resistance. We first focused on the development of two major classes of antimicrobials still currently used for the treatment of Gram-negative bacteria, such as fluoroquinolones and carbapenemes. Subsequently, we directed our attention to the growth of the incidence of infections due to Methicillin-Resistant Staphylococcus aureus (MRSA). Although the first MRSA was already isolated in 1961, the treatment of this new pathogen has been based on the efficacy of vancomycin for more than four decades. Only in the last 15 yr, we assisted in the development of new antimicrobial agents such as linezolid and daptomycin.